2009
DOI: 10.1007/s11011-008-9130-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and the brain

Abstract: There is growing evidence that hepatitis C virus (HCV)-infection may affect the brain. About half of the HCV-infected patients complain of chronic fatigue irrespective of their stage of liver disease or virus replication rate. Even after successful antiviral therapy fatigue persists in about one third of the patients. Many patients, in addition, report of deficits in attention, concentration and memory, some also of depression. Psychometric testing revealed deficits in attention and verbal learning ability as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 34 publications
5
55
1
5
Order By: Relevance
“…Further findings have shown [60] a lower level of NAA/Cr ratio in the frontal grey matter of HCVpatients without any change in the Cho/Cr ratio. Both findings have suggested the occurrence of an increased cell membrane turnover and reduced neuronal function [27] . Use of ondansetron which is a competitive antagonist of serotonin receptors has ameliorated fatigue in HCV infected patient.…”
Section: Mechanisms Contributing To Neurological Dysfunctionmentioning
confidence: 98%
See 2 more Smart Citations
“…Further findings have shown [60] a lower level of NAA/Cr ratio in the frontal grey matter of HCVpatients without any change in the Cho/Cr ratio. Both findings have suggested the occurrence of an increased cell membrane turnover and reduced neuronal function [27] . Use of ondansetron which is a competitive antagonist of serotonin receptors has ameliorated fatigue in HCV infected patient.…”
Section: Mechanisms Contributing To Neurological Dysfunctionmentioning
confidence: 98%
“…In a study on 37 HCV infected patients without other complications by McAndrews et al [26] , verbal learning impairment and lack of attention were observed. A correlation of cognitive impairment and fatigue with HCV infection was observed in half of the patients observed in a study conducted by Weissenborn et al [27] , comparing neuropsychological functioning of HCV positive patients with normal liver function; though in another study by Montagnese et al [28] , an exceptionally high incidence of fast (βdominated) electroencephalograms was documented.…”
Section: Neurophysiological Symptomsmentioning
confidence: 98%
See 1 more Smart Citation
“…There are several studies demonstrating the presence of the HCV virons both in the CSF and brain tissue of patients with HCV infection [5]. Nonetheless, the link between direct central nervous system infection and the development of vasculitic lesions of the brain is weak.…”
Section: Commentmentioning
confidence: 99%
“…Further factors that may impact the results of neuropsychological or neurophysiological methods used for diagnosing minimal HE are the disorders underlying liver cirrhosis such as alcoholism [35], hepatitis C virus infection [36] or primary biliary cirrhosis, for example [37].…”
Section: Diagnosis Of Minimal Hementioning
confidence: 99%